Differentiation of Bone Marrow Mesenchymal Stem Cells into Chondrocytes after Short Term Culture in Alkaline Medium - Moghadam, Farshad Homayouni (Int J Hematol Oncol Stem Cell Res, 2014)
BACKGROUND: Bone marrow mesenchymal stem cells (MSCs) are one of the undifferentiated multipotential cell sources of human body. MSCs have the capacity to form a variety of cell types, especially chondrocytes and osteocytes. Learning about responses of MSCs to external milieu and chemical factors such as pH could recommend new approaches for preparation of suitable scaffolds for bone and cartilage tissue engineering. In present study, the effect of alkaline medium on chondrogenic and osteogenic differentiation of rat MSCs was evaluated METHODS: MSCs were harvested from bone marrow of animals and then the response of passage1 and 2 of MSCs (P1 MSCs & P2 MSCs) to the culture in alkaline medium (pH: 8) was evaluated. Cytochemical and immunocytochemical staining were performed to distinguish chondrocytes and osteocytes. Real-time PCR was performed to evaluate the type II collagen and osteopontin mRNA levels. RESULTS: Staining for type II collagen, a chondrocytic specific marker, revealed that after one-week culture in alkaline medium, a considerable amount of P1 MSCs had shown chondrocytic morphology. By prolonging the culture period up to 4 weeks, osteogenic cells with expanded matrix and mineralized areas around them were appeared. Results of real-time PCR showed that P1 MSCs after one week culture in alkaline medium expressed highest rate of type II collagen and osteopontin mRNA among all groups. CONCLUSION: This study demonstrated that alkaline medium is a potent chondrogenic differentiation inducer for MSCs in their first passage.